Implementation of computer image analysis to evaluate leg ulcer treatment – preliminary study - Kwiecień, Aneta; Zalewska-Janowska, Anna; Strzelecki, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
Leg ulcers result from venous, arterial or lymphatic blood vessel disturbances. Literature data print out of image analysis usefulness in evaluation of different skin diseases. The aim of this study was to elaborate new techniques of image analysis based on photographic and digital image data for evaluation of leg ulcers extensivity and treatment progress. Twenty female patients aged 60-80 years, hospitalized at the Department of Dermatology, Medical University of Lodz, were selected for the study. The patients were on vasodilative drugs and locally purifying agents and finally components promoting granulation have been were applied. Subsequent photos were taken every 10-14 days depending on the healing process. It was observed that fairly small ulcers were the most suitable for image analysis both automatic and manual. The patients were satisfied with the possibility of skin lesion treatment monitoring.